Features of Telerehabilitation and Considerations for Resource-Limited Settings: A Scoping Review. - Kelly, Emily; Tingey, Jamie L.; Ott, C. Jessica; Hahn, Helena; Bentley, Jacob A.; Wegener, Stephen T.; Zaidi, Zehra; Zia, Nukhba; Bachani, Abdulgafoor M. (Disability, CBR & Inclusive Development)
Aim: The global need for rehabilitation is extensive yet remains significantly unmet. Health systems, especially in low- and middle-income countries (LMICs), lack structures and resources to address the rapidly growing need for rehabilitation services. Telerehabilitation offers an innovative approach to narrow health systems gaps and facilitate rehabilitation services. Few studies have investigated features and functionalities used in telerehabilitation, especially regarding implications for resource-limited settings and LMICs. This scoping review aims to identify technological features and functionalities used to deliver telerehabilitation, map them onto clinical care processes, and outline gaps and directions for future research, especially regarding considerations for resource-limited settings. Methods: This study utilized the PRISMA- checklist. Six databases were searched (PubMed, Embase, Scopus, CINAHL, Compendex, NARIC) to identify articles that described the remote delivery of rehabilitation services. Three reviewers screened and selected relevant publications. Descriptive statistics and qualitative content analysis were used to analyze full-text articles. Results: 135 articles were included in the full-text review. The publication year ranged from 1997 to 2021. The most frequently identified telerehabilitation feature was "data collection," followed by "videoconferencing," and "messaging." Features mapped onto six clinical categories, with "implementation" accounting for 41% of all features, Only 18% of articles focused on LMICs. Few papers included a comprehensive platform of features, discussed integration into health systems, or included financial analyses. Conclusions: Diverse technological tools exist for the remote delivery of rehabilitation services, but few cohesive platforms offer features across multiple clinical categories. Additionally, high income countries are overwhelmingly represented in the literature. Future directions for research include expanded focus on resource-limited settings and LMICS, discussion about financial considerations, and attention to health systems integration. Limitations: The generalizability of our findings are limited given the rapid growth of literature on telerehabilitation and continued development of apps and platforms since the time of review.